The Effects of Chronic Asprosin Administration on Monoamine Levels in the Arcuate Nucleus, Ventromedial Hypothalamus and Dorsomedial Hypothalamus Regions - Ozdede, Mehmet Ridvan; Kacar, Emine; Oz, Zeynep Dila; Ozgen, Aslisah; Serhatlioglu, Ihsan; Yilmaz, Bayram; Kelestimur, Haluk (Wiley, 2023)
[Abstract Not Available]
Keywords: Asprosin; Monoamine; Arcuate nucleus (ARC); Ventromedial hypothalamus (VMH); Dorsomedial hypothalamus (DMH); High-performance liquid chromatography (HPLC)